The Concept of the Teacher in Ki Hajar Dewantara's Thought and Its Relevance to Buddhism - Sugeng Sugeng; Agus Subandi; Khe Foon Hew (Edukasi, 2023)
Abstract____________________________________________________________The purpose of this study is to examine the concept of the teacher in Ki Hajar Dewantara's thinking and its relevance to Buddhism, driven by the prevalent occurrences of immoral behavior among educators. This research adopts a literature review methodology, utilizing a content analysis approach. The data sources for this study consist of both primary and secondary sources. Primary sources include the works of Ki Hajar Dewantara and the Buddhist scriptures (Tipitaka). Secondary sources encompass writings about Ki Hajar Dewantara and studies related to education in Buddhism. The data collection process involves employing library research techniques. The collected data is subjected to qualitative analysis, specifically an inductive approach, which involves drawing insights and patterns from the data to address the research problem at hand. According to Ki Hajar Dewantara, the concept of the teacher is highly relevant to Buddhism. It emphasizes the notion of teachers as role models who possess not only knowledge and skills but also high moral standards and wisdom. Ki Hajar Dewantara highlights the significance of teachers as exemplars, capable of inspiring and guiding students through their own conduct and actions. In line with Buddhist teachings, a teacher should embody the qualities they seek to instill in their students. This includes not only intellectual capabilities but also ethical conduct, virtues, and wisdom. The alignment between Ki Hajar Dewantara's concept of the teacher and Buddhism reinforces the need for educators to uphold moral values and personal development. It addresses the issue of immoral behavior among educators by emphasizing the importance of teachers as individuals who possess a holistic set of abilities encompassing knowledge, skills, morality, and wisdom. By examining primary and secondary sources, this study provides a comprehensive understanding of the concept of the teacher in Ki Hajar Dewantara's thinking and its relevance to Buddhism. The findings of this research contribute to the discourse on education, ethics, and the role of teachers in society, highlighting the importance of cultivating not only intellectual growth but also moral character and wisdom in educational settings.